Wind tunnel site analysis of Dow Chemical Facility at Rocky Flats, Colorado - Meroney, R. N., author; Chaudhry, F. H., author (Colorado State University. Libraries, 1972)
Tests were conducted on a model of the Dow Chemical Company plutonium recovery facility, Rocky Flats Division, and the surrounding topography to determine the dispersal and trajectories of potential effluents. Profiles of wind and turbulence over the facility were adjusted to forms expected for the given terrain. Dispersion and trajectory characteristics were determined by releasing a krypton-85 tracer gas from specific sources and sampling the plume downwind. Results suggest that the plumes depart only modestly from behavior suggested by the Pasquill-Gifford prediction methods. All results are tabulated and/or presented in a dimensionless manner suitable for prototype site evaluation.
CER71-72RNM-FC-451.
May 1972.
Prepared for Research and Ecology, Rocky Flats Division, Dow Chemical Company.
Keywords: Dow Chemical Company. Rocky Flats Division; Wind tunnel models